Types and concentrations of blood-based biomarkers in adults with peripheral neuropathies: a systematic review and meta-analysis - Fundaun, J; Kolski, M; Molina-Álvarez, M; Baskozos, G; Schmid, AB (American Medical Association, 2022)
Importance Peripheral neuropathies are common conditions and can result in numbness, paresthesia, motor deficits, and pain. There is increasing evidence for the use of biomarkers as clinical indicators of the presence, severity, and prognosis of nerve lesions; however, biomarker identification has largely been focused on disorders of the central nervous system, and less is known about their role in the peripheral nervous system.